Gastrointestinal Interventions: Then and Now - LoGiurato, Brendan; Smirniotopoulos, John; Darcy, Michael; Charalel, Resmi A. (Digestive Disease Interventions, 2020)
Gastrointestinal interventions have continuously evolved since the inception of interventional radiology. This article will review major milestones in this evolution including the introduction of new tools, the development of new procedures, and the establishment of interventional radiology as its own clinical specialty. Together, these milestones have helped shape how interventional radiologists perform gastrointestinal interventions today.
Keywords: gastrointestinal interventions; history; interventional radiology